Risk Factors for the Occurrence of Cutaneous Neoplasms in Dogs: A Retrospective Study by Cytology Reports, 2019–2021 - Issa Carolina García-Reynoso; Cesar Augusto Flores-Dueñas; Nohemí Castro-del Campo; Mariana Jácome-Ibarra; José Carlomán Herrera-Ramírez; Sergio Daniel Gómez-Gómez; Miguel Ángel Rodríguez-Gaxiola; Soila Maribel Gaxiola-Camacho (Animals)
Studies worldwide report cutaneous neoplasms in dogs; however, data in the arid regions of Mexico remain scarce. Here we report the main malignant cutaneous neoplasms diagnosed by fine needle aspiration cytology (FNAC), and describe the associations with age, sex and breed in Mexicali. Neoplastic lesions accounted for 25.52% (698/2735) of the cases, of which 56.59% (395/698) were malignant. The highest prevalence was observed in dogs aged 9–12 years (n = 193), intact males (n = 162), and mixed-breed dogs (n = 247). Round cell neoplasms (n = 309), including lymphoma, transmissible venereal tumors (TVT), and mast cell tumors (MCT), were the most common cell lineage. Using dogs aged 0–4 years as the reference group, dogs aged 9–12 years had 0.241 times the odds of developing malignant neoplasms (95% CI: 0.141–0.415, p = 0.0025). Using neutered males as the reference group, intact females showed 2.499 times the odds of developing malignant neoplasms (95% CI: 1.462–4.271, p = 0.0042). Compared to mixed-breed dogs, Schnauzers (OR = 0.161) showed significantly lower odds of malignancy (95% CI: 0.082–0.317, p = 0.0004), while Pitbull Terriers had 1.748 times more chance of present malignant neoplasia (95% CI: 1.014–3.013, p < 0.0001). This study provides significant epidemiological evidence on canine cutaneous neoplasms in an arid region of Mexico, identifying key risk factors and distribution patterns that can guide preventive, diagnostic, and therapeutic strategies tailored to regional characteristics.